2007
DOI: 10.1074/jbc.c700153200
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Selected for the Protein Nanocage Pores Change the Rate of Iron Recovery from the Ferritin Mineral

Abstract: Pores regulate access between ferric-oxy biomineral inside and reductants/chelators outside the ferritin protein nanocage to control iron demineralization rates. The pore helix/loop/ helix motifs that are contributed by three subunits unfold independently of the protein cage, as observed by crystallography, Fe removal rates, and CD spectroscopy. Pore unfolding is induced in wild type ferritin by increased temperature or urea (1-10 mM), a physiological urea range, 0.1 mM guanidine, or mutation of conserved pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 42 publications
0
81
0
2
Order By: Relevance
“…Increasing temperature, physiological concentration of chaotropic reagents or site-directed mutagenesis of specific residues of tadpole M-ferritin (Leu-110, Arg-72 an d Asp-122) have been shown to dramatically increase the in vitro rate of ferritin iron release by altering the stability of the 3-fold channels. Furthermore, the screening of a combinatorial library brought to the identification of peptides capable of binding to ferritin, opening or closing the pores and thus modulating the rate of iron release (Liu et al 2007). This finding led to the speculative proposal of regulatory molecules controlling the breathing of the gated pores in vivo.…”
Section: Mammalian Ferritin Structurementioning
confidence: 99%
“…Increasing temperature, physiological concentration of chaotropic reagents or site-directed mutagenesis of specific residues of tadpole M-ferritin (Leu-110, Arg-72 an d Asp-122) have been shown to dramatically increase the in vitro rate of ferritin iron release by altering the stability of the 3-fold channels. Furthermore, the screening of a combinatorial library brought to the identification of peptides capable of binding to ferritin, opening or closing the pores and thus modulating the rate of iron release (Liu et al 2007). This finding led to the speculative proposal of regulatory molecules controlling the breathing of the gated pores in vivo.…”
Section: Mammalian Ferritin Structurementioning
confidence: 99%
“…Available information suggests that a cytosolic iron chaperone Poly (rC)-binding protein 1 binds cytosolic iron for delivery to ferritin (398). Poorly characterized ferritin-binding proteins, amino acids, and small molecules regulate the release of iron from ferritin, supporting the gated pore model (273,274,427). Stored iron is released in response to low intracellular iron, thus maintaining equilibrium between ferritin iron and the labile iron pool.…”
Section: A Ferritin and Ferritinopathiesmentioning
confidence: 99%
“…Also, the protein channels that facilitate Fe 2ϩ exit could play an important role. For example, in eukaryotic ferritins, it has been shown that the 3-fold channels can undergo localized "melting" in response to environmental changes (such as low chaotrope concentration, temperature, and specific peptide-ferritin interactions), such that iron release can be considered to be "gated" (40,55,56). Whether such mechanisms that could affect the access of reductant to the ferric mineral also exist in BFRs is not clear, but we note that several of the residues important for channel melting in eukaryotic ferritin are conserved.…”
Section: Reductant and Chelator Dependence Of Bfr Iron Releasementioning
confidence: 99%